PERAN PIMPINAN MEMOTIVASI BAWAHAN MELANJUTKAN PENDIDIKAN S2 DI LINGKUNGAN KERJA PEMERINTAH KECAMATAN SE-KOTA PONTIANAK ISMAIL, SULISTYARINI, IMRAN - Ismail, Ismail; Sulistyarini, Sulistyarini; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:This research aims to know the role of chairman in motivating subordinate continuing magister program (S2) in workplace of sub district government of whole Pontianak city. The method is descriptive by qualitative approach. The sources of data primary and secondary datas. The techniques used of the research are observation, direct communication, and documentary study. The result of the research is the chairman's roles as a motivator are doing Coffee Morning, Friday Clean, but it furthermore leads to be personal motivation in this case. The chairman's role as a commander focuses on giving duties and having responsibilities according to duty details and the target which reached and budgeting that has tobe managed and being responsible for, it's implemented to letter of treaty, between sub-district head and the subordinates. The chairman's role as as controller by controlling the subordinates' skill in communicating by talking each other well mannered and friendly, giving explanation, punctuation, and integrity in supporting prime service to society. The chairman's role as a communicator promotes the subordinates whose the good achievements and enough conditions will get the opportunity to run a higher position. Keywords: Role of Leader, Motivation, and Continuing Education S2